2019
DOI: 10.3390/cancers11071015
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Antitumor Effects and Autophagy Induction as a Resistance Mechanism by Cytotoxics and EZH2 Inhibition in INI1-Negative Epithelioid Sarcoma Patient-Derived Xenograft

Abstract: Epithelioid sarcoma (ES) is a rare mesenchymal malignancy marked by SMARCB1/INI1 deficiency. Retrospective clinical data report on the activity of anthracycline- and gemcitabine-based regimens. EZH2 inhibitors are currently being tested in clinical trials. Since comparisons of these agents are unlikely to be prospectively evaluated in the clinics, we took advantage of an INI1-deficient proximal-type ES patient-derived xenograft (PDX ES-1) to comparatively assess its preclinical antitumor activity. Mice were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…( 72 ) Besides a role for HMGA2 in negatively regulating MSC differentiation to ostb, it may play a protective role in the skeleton ( 74 ) at later steps in differentiation of ostb to osteocytes and in osteocyte homeostasis by helping to induce autophagy. ( 71,75,76 )…”
Section: Discussionmentioning
confidence: 99%
“…( 72 ) Besides a role for HMGA2 in negatively regulating MSC differentiation to ostb, it may play a protective role in the skeleton ( 74 ) at later steps in differentiation of ostb to osteocytes and in osteocyte homeostasis by helping to induce autophagy. ( 71,75,76 )…”
Section: Discussionmentioning
confidence: 99%
“…Of 62 treated participants, with a median of 1 prior therapy, 15% exhibited partial responses with objective response rate and disease control rate of 15% and 26%, respectively. The duration of response to the treatment ranged from 7.1 to 103.0 weeks and a median overall survival of 82.4 weeks was observed for all 62 patients [60] .…”
Section: Epithelioid Sarcomamentioning
confidence: 99%
“…A study involving patient-derived INI1-negative ES tumour samples xenotransplanted to immunodeficient mice and administration of EPZ011989 resulted in tumour growth stabilization at first, followed by tumour volume inhibition of up to 89% and decreased H3K27me3 [60,61] . A clinical trial of patients with SMARCB1(INI1)-negative ES treated with tazemetostat showed similar results to SS patients.…”
Section: Epithelioid Sarcomamentioning
confidence: 99%
“…ere are a number of studies based on patient-derived cells (PDC) and patient-derived xenograft (PDX) model in vivo. However, most of the described investigations are focused on establishment of new cell line derived from patient tumor (for example, see [63][64][65][66][67], on preclinical studies of novel or repurposed drug/combination of drugs in vitro [68][69][70][71] and in vivo [72][73][74]). Only a few studies address the optimization of STS treatment.…”
Section: Drug Sensitivity Testing On Patient-derived Sts Cellsmentioning
confidence: 99%